Application of 3D Balanced Growth Theory to the Formation of Bulk Amorphous Alloys - Wu, YaQi; Zhang, Yong; Zhang, Tao (Frontiers in Materials, 2021)
Since the emergence of amorphous alloys as a new class of materials, efficiency improvements have been made in optimizing the fabrication process, the mechanization of alloy formation, and the size of the alloys themselves. Amorphous alloys have been used in precision instruments as they possess excellent magnetic properties, corrosion resistance, wear resistance, high strength, hardness, toughness, high electrical resistivity, and electromechanical coupling properties. Because their hysteresis losses are lower than those of traditional transformer cores, the conversion efficiency of equipment has been significantly improved, thereby saving energy and protecting the environment. Hence, amorphous iron cores have replaced traditional materials. Amorphous alloys also show excellent performance as anti-corrosion and wear-resistant coatings. The process of preparing amorphous alloys starts with an amorphous alloy film obtained by evaporation deposition and then proceeds to the use of a high cooling rate ribbon spinning method to finally obtain a thin strip of an amorphous alloy. A widely used method of copper mold suction casting is then used to prepare the bulk amorphous alloy. The sizes of amorphous alloys have been continually increasing, which has resulted in increasingly serious challenges, such as cooling rate and thermal stability limitations. In addition, crystals can form at low cooling rates. The latent heat of crystallization is released when crystals are formed, which causes damage to the amorphous area so that the size of amorphous alloys is reduced. Because of these difficulties, new processes that eliminate the cooling rate gradient, such as 3D additive manufacturing, ultrasonic production, and mold design, combined with the concept of “entropy control” component design and the economic theory of “balanced development,” lead to a three-dimensional bulk amorphous alloy being proposed. The theory of balanced growth provides a new concept for the development and application of bulk amorphous alloys. This review offers a retrospective view of recent studies of amorphous alloys and provides a description of the formation of amorphous alloys and amorphous phases and the criteria required to predict the successful formation of amorphous alloys. Then, we address the problem of size limitation confronting current production methods. The three-dimensional balanced growth theory of bulk amorphous alloys was formulated from a flexible adaptation of the balanced growth theory of economics. We have confidence that the production and development of bulk amorphous alloys have a bright future.